Combined Antimicrobial Effect of Thymol and Sodium Lactate against Listeria monocytogenes and Salmonella Typhimurium in Fish Patty - Ilhak, Osman Irfan; Guran, Husnu Sahan (Wiley, 2014)
The purpose of this study was to evaluate the antimicrobial efficacy of the combinations of thymol (0.1 w/w) and sodium lactate (1 and 2% v/w) against Listeria monocytogenes and Salmonella Typhimurium in fish patty samples stored at 4C for 5 days. Treatment with the combination of 0.1% thymol+2% sodium lactate did not show a significant inhibition on the L.monocytogenes when compared with the sample treated with 2% sodium lactate alone. However, treatment of fish patty with the combination of 0.1% thymol+2% sodium lactate showed a synergistic effect on Salmonella Typhimurium on days 3 and 5 of storage. Practical Applications L.monocytogenes and Salmonella spp. are among the most important foodborne pathogens. Today, compounds with antimicrobial property have found common use in the control of these pathogens and their elimination from foods. Only small percentages of essential oils are tolerable in foods, since essential oils may negatively affects the organoleptic properties of foods. Therefore, combinations of essential oils with other preservatives may help to minimize the application concentrations required. The findings of the present study indicate that combination of 0.1% thymol+2% sodium lactate would have a synergistic effect against Salmonella Typhimurium in fish patty.
Keywords: Essential Oil Combinations; Rainbow-Trout; Organic-Acids; Carvacrol; Efficacy; Nisin; Mechanism; Quality; Acetate; Citrate